An Internet-based system for the commerce of medical devices. A portal for improving communication between healthcare professionals and the medical device industry. - Palamas, S.
The MEDIDEV service combines a central product catalog featuring basic information with Internet-connected websites and online catalogs hosting the detailed information. This approach is compatible with the manufacturers' requirement to maintain control over the detailed information of their products. At the same time, it allows the end user to efficiently choose from a potentially long list of products-those which mostly satisfy his requirements-and then to get more detailed information in the corresponding linked websites and on-line catalogs. The manufacturers have two alternative ways for updating the information stored in the Portal. They can use a human-operated and HTML-based interface or an automated and CORBA-based interface. Thus, the timeliness and consistency of the Portal information is ensured. The adoption of Internet standard technologies (Java, CORBA, XML) has maintained a high level of platform independence and interoperability. The current version has been developed for Windows NT, while the final version is currently ported to a HP UNIX machine. Special care has been taken to support both major Internet browsers: Internet Explorer and Netscape Navigator. The implementation of XML for the data presentation has led to a reduced and optimized transmission of data from the Portal to the user's browser. Only the new data are transmitted as XML documents each time, while formatting information is once loaded at the browser. The separation of data from the formatting information leads to another advantage. It is a common practice today for horizontal portals, which are targeting a wide variety of interests, to subcontract content from other, more specialized portals or sites (vertical portals). The MEDIDEV Portal can provide its data to other sites as XML documents that will be parsed and displayed with their own look and feel. This opens up new marketing opportunities.
Keywords: CORBA-based interface; HTML-based interface; Internet Explorer; Internet-based system; Java; MEDIDEV service; Netscape Navigator; Windows NT; XML documents; Communication between healthcare professionals improvement; Human-operated interface; Information updating; Linked websites; Marketing opportunities; Medical device industry; Medical devices commerce; On-line catalogs